Juridical Analysis Of Legal Protection For The Victims Of Artificial Intelligence Misuse Based On Indonesia’s Law - Norma Kinanty; Bambang Santoso (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
This journal focused on the juridical analysis of legal protection for the victims of Artificial Intelligence misuse based on Indonesia’s Law. In this context, AI misuse refers to the use of AI technology that harms an individual or group, physically, mentally, and financially. Firstly, this journal explored how Indonesia’s law protects the victims of AI misuse. Although Indonesia has developed some regulations and policies, the legal protection of the victims of AI misuse still has become a challenge. The existing laws did not cover the specific aspects of AI misuse, including data privacy, algorithm discrimination, and other social impacts. Secondly, this journal discussed the challenges and obstacles in implementing legal protection for the victims of AI misuse in Indonesia. Some vital challenges included the lack of a general understanding of AI, specific laws for AI, and the gaps between the technology advancement and the existing law. Moreover, another challenge came from the lack of an international law framework that regulates the use of AI. This journal suggested the need for regulation improvement, public education about AI, and international cooperation in regulating AI. Besides, further research is needed to understand the bad impact of AI misuse and how the law can be more effective in protecting the victims.